2017
DOI: 10.1007/s00395-017-0666-6
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis to identify mechanisms underlying heart failure susceptibility in mice and humans

Abstract: Genetic factors are known to modulate cardiac susceptibility to ventricular hypertrophy and failure. To determine how strain influences the transcriptional response to pressure overload-induced heart failure (HF) and which of these changes accurately reflect the human disease, we analyzed the myocardial transcriptional profile of mouse strains with high (C57BL/6J) and low (129S1/SvImJ) susceptibility for HF development, which we compared to that of human failing hearts. Following transverse aortic constriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 74 publications
3
27
0
Order By: Relevance
“…There are several studies that have suggested that measurement of periostin may be of prognostic value. Such an association has been reported in CAD, HF, MI, and CVDs . In contrast, other study suggested that systemic periostin levels are largely determined by underlying pathogenesis of variety of cancer and allergic diseases, including asthma rather than cardiac function, and that prognostic significance does not remain after adjustment for underlying cardiac function .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…There are several studies that have suggested that measurement of periostin may be of prognostic value. Such an association has been reported in CAD, HF, MI, and CVDs . In contrast, other study suggested that systemic periostin levels are largely determined by underlying pathogenesis of variety of cancer and allergic diseases, including asthma rather than cardiac function, and that prognostic significance does not remain after adjustment for underlying cardiac function .…”
Section: Discussionmentioning
confidence: 83%
“…Patients with end‐stage dilated cardiomyopathy who underwent transplantation, with healthy control as a donor group. The periostin expression was upregulated almost fivefold in human failing hearts …”
Section: Resultsmentioning
confidence: 99%
“…50 These were also tested in mice. [51][52][53] In contrast to suture-based TAC or ORAB, clips do not induce a circular constriction as the aorta is asymmetrically distorted. Since the aorta is compressed rather than constricted, the total crosssectional area at the stenosis is difficult to control.…”
Section: Discussionmentioning
confidence: 99%
“…Clips adjusted to 27, 30, and 32G needles have been applied without achieving reproducible, graded cardiac remodelling and dysfunction. [51][52][53] We, therefore, believe that the constriction obtained with ORAB is superior to clipconstriction with regards to stenosis standardization.…”
Section: Discussionmentioning
confidence: 99%
“…Protein-protein network analysis and visualizations were performed using Cytoscape (3.7.2). Literature-curated pathway enrichment was achieved using QIAGEN's Ingenuity Pathway Analysis (IPA R , QIAGEN Redwood City, www.qiagen/ingenuity) on differentially expressed proteins using a low-stringency statistical threshold of p < 0.05, followed by Benjamini-Hochberg (BH) post-hoc adjustment, as published previously (24). To perform the enrichment, unfiltered differential expression data of all 3 comparisons were first merged into a single data matrix for uploading to IPA via Uniprot identifier.…”
Section: Bioinformatics and Data Visualizationmentioning
confidence: 99%